Enhancing Heat Exchangers with Graphene as Al2O3 Nanofluid Coatings - Biswajit Choubey,; H.S. Sahu, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
A well-designed heat exchanger improves the effectiveness of the heat exchanger. A hairpin heat exchanger resembles a hairpin when a shell-and-tube heat exchanger with a single-pass unit is folded in half, which can be used where space is a constraint. Design, CFD analysis and evaluation of various parameters of hairpin heat exchanger with graphene layer and its comparison with hairpin heat exchanger without graphene layer is the main aim of this paper. The heat exchanger is modified with the addition of a graphene layer on both the side (inner and outer side) of the tube of the heat exchanger. Graphene is an allotropic form of carbon having a single layer of atoms distributed in a 2-D honeycomb lattice. The coefficient of thermal conductivity of graphene is very high as compared to other materials. In addition to it, nanofluid Al2O3 is introduced as cold fluid. Nanofluids are colloidal suspensions made of nanoparticles in some base fluid. ANSYS FLUENT 2020 has been used to model the geometry and to perform numerical simulation. Turbulent flow conditions were used to analyse the heat exchanger. CFD analysis has been done on hairpin heat exchangers using graphene layer. The results indicate that the high thermal conductivity of graphene increases rate of heat transfer, and the numerical value of convective heat transfer coefficient is also high.
Keywords: Hair Pin Heat Exchanger; Graphene; Nanofluid; Thermal Analysis; Convective Heat Transfer Coefficient